FMixFN: A Fast Big Data-Oriented Genomic Selection Model Based on an Iterative Conditional Expectation algorithm - Xu, Wenwu; Liu, Xiaodong; Liao, Mingfu; Xiao, Shijun; Zheng, Min; Yao, Tianxiong; Chen, Zuoquan; Huang, Lusheng; Zhang, Zhiyan (Frontiers in Genetics, 2021)
Genomic selection is an approach to select elite breeding stock based on the use of dense genetic markers and that has led to the development of various models to derive the prediction equation. However, the current genomic selection software faces several issues such as low prediction accuracy, low computational efficiency, or inability to handle large-scale sample data. We report the development of a genomic prediction model named FMixFN with four zero-mean normal distributions as the prior distributions to optimize the predictive ability and computing efficiency. The variance of the prior distributions in our model is precisely determined based on an F2 population, and genomic eatimated breeding values (GEBV) can be obtained accurately and quickly in combination with an iterative conditional expectation algorithm. We demonstrated that FMixFN improves computational efficiency and predictive ability compare to other popular methods, such as GBLUP, SSgblup, MIX, BayesR, BayesA, and BayesB. Most importantly, FMixFN may handle large-scale sample data, and thus should be able to meet the needs of large breeding companies or combined breeding schedules. Our study developed a Bayes genomic selection model called FMixFN, which combines stable predictive ability and high computational efficiency, and is a big data-oriented genomic selection model that has potential in the future. FMixFN method can be freely accessed at https://zenodo.org/record/4383745 (DOI: 10.5281/zenodo.4383745).